Reaction of Acyl Chlorides with In Situ Formed Zinc Selenolates: Synthesis of Selenoesters versus Ring-Opening Reaction of Tetrahydrofuran - Gemma Bellino; Marialaura Scisciani; Jaqueline Pinto Vargas; Luca Sancineto; Luana Bagnoli; Francesca Marini; Diogo Seibert Lüdtke; Eder Joao Lenardao; Claudio Santi (Journal of Chemistry)
Attempting to apply the in situ production of PhSeZnSePh to the synthesis of selenoesters, an unexpected reaction involving the solvent (tetrahydrofuran) was observed and studied. We reported here some evidences about the mechanism and the possibility to control the chemoselectivity of this new reaction that afforded the formation of interesting selenoderivatives in which the selenium moiety and the carboxylic one are spaced by four carbon units.